Scavenging Circulating Mitochondrial DNA as a Potential Therapeutic Option for Multiple Organ Dysfunction in Trauma Hemorrhage - Aswani, Andrew; Manson, Joanna; Itagaki, Kiyoshi; Chiazza, Fausto; Collino, Massimo; Wupeng, Winston Liao; Chan, Tze Khee; Wong, W. S. Fred; Hauser, Carl J.; Thiemermann, Chris; Brohi, Karim (Frontiers in Immunology, 2018)
Trauma is a leading cause of death worldwide with 5.8 million deaths occurring yearly. Almost 40% of trauma deaths are due to bleeding and occur in the first few hours after injury. Of the remaining severely injured patients up to 25% develop a dysregulated immune response leading to multiple organ dysfunction syndrome (MODS). Despite improvements in trauma care, the morbidity and mortality of this condition remains very high. Massive traumatic injury can overwhelm endogenous homeostatic mechanisms even with prompt treatment. The underlying mechanisms driving MODS are also not fully elucidated. As a result, successful therapies for trauma-related MODS are lacking. Trauma causes tissue damage that releases a large number of endogenous damage-associated molecular patterns (DAMPs). Mitochondrial DAMPs released in trauma, such as mitochondrial DNA (mtDNA), could help to explain part of the immune response in trauma given the structural similarities between mitochondria and bacteria. MtDNA, like bacterial DNA, contains an abundance of highly stimulatory unmethylated CpG DNA motifs that signal through Toll-like receptor (TLR)-9 to produce inflammation. MtDNA has been shown to be highly damaging when injected into healthy animals causing acute organ injury to develop. Elevated circulating levels of mtDNA have been reported in trauma patients but an association with clinically meaningful outcomes has not been established in a large cohort. We aimed to determine whether mtDNA released after clinical trauma haemorrhage is sufficient for the development of MODS. Secondly, we aimed to determine the extent of mtDNA release with varying degrees of tissue injury and haemorrhagic shock in a clinically relevant rodent model. Our final aim was to determine whether neutralising mtDNA with the nucleic acid scavenging polymer, Hexadimethrine bromide, at a clinically relevant time point in vivo would reduce the severity of organ injury in this model. Conclusions: We have shown that release of mtDNA is sufficient for the development of multiple organ injury. MtDNA concentrations likely peak at different points in the early postinjury phase dependent on the degree of isolated trauma vs combined trauma and haemorrhagic shock. Hexadimethrine bromide scavenging of circulating mtDNA (and nDNA) is associated with rescue from severe multiple organ injury in